The dominant animal : stories - Scanlan, Kathryn, 1980- (MCD x FSG Originals / Farrar, Straus and Giroux, 2020)
"In The Dominant Animal--Kathryn Scanlan's adventurous, unsettling debut collection--compression is key. Sentences have been relentlessly trimmed, tuned, and teased for maximum impact, and a ferocious attention to rhythm and sound results in a palpable pulse of excitability and distress. The nature of love is questioned at a golf course, a flower shop, an all-you-can-eat buffet. The clay head of a man is bought and displayed as a trophy. Interior life manifests on the physical plane, where characters--human and animal--eat and breathe, provoke and injure one another. With exquisite control, Scanlan moves from expansive moods and fine afternoons to unease and violence--and also from deliberate and generative ambiguity to shocking, revelatory exactitude. Disturbances accrue as the collection progresses. How often the conclusions open--rather than tie--up. How they twist alertly. No mercy, a character says--and these stories are merciless and strange and absolutely masterful."--